On‐Surface Synthesis of Polyphenylene Wires Comprising Rigid Aliphatic Bicyclo[1.1.1]Pentane Isolator Units. Issue 19 (30th March 2023) - Yang, Biao; Niu, Kaifeng; Cao, Nan; Grover, Nitika; Zhao, Wenchao; Riss, Alexander; Björk, Jonas; Auwärter, Willi; Barth, Johannes V.; Senge, Mathias O.
Abstract: Bicyclo[1.1.1]pentane (BCP) motifs are of growing importance to the pharmaceutical industry as sp 3 ‐rich bioisosteres of benzene rings and as molecular building blocks in materials science. Herein we explore the behavior of 1, 3‐disubstituted BCP moieties on metal surfaces by combining low‐temperature scanning tunneling microscopy / non‐contact atomic force microscopy studies with density functional theory modeling. We examine the configuration of individual BCP‐containing precursors on Au(111), their supramolecular assembly and thermally activated dehalogenative coupling reactions, affording polymeric chains with incorporated electronically isolating units. Our studies not only provide the first sub‐molecular insights of the BCP scaffold behavior on surfaces, but also extend the potential application of BCP derivatives towards integration in custom‐designed surface architectures. Abstract : Polyphenylene wires regularly substituted with rigid aliphatic bicyclopentane isolators were obtained by on‐surface synthesis and characterized with submolecular precision.